Ytterbium-doped TeO2-ZnO-Na2O glasses: Insights into physical, mechanical, and optical properties - Devara Ega Fausta; Agus Supriyanto; Ahmad Marzuki; Fahru Nurosyid; Rachmat Hidayat; Saidatul Nisya; Kharenina Zalfa' Shalihah (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2026)
This present study constitutes a systematic investigation imto the influence of low-concentration Yb2O3 incorporation on the physical, mechanical, and optical properties of TeO2 ZnO Na2O (TZN) glasses. The glasses under consideration are composed of 65TeO2-(30-x)ZnO-5Na2O- xYb2O3 (x = 0-2.5 mol%). The fabrication process utilized the conventional melt-quenching technique. The present study specifically addresses the limited understanding of how minor Yb3+ incorporation affects the structure-property relationships in TZN glass systems. The results obtained demonstrate progressive densification of the glass network in the presence of increasing Yb2O3 content. This is evidenced by an increase in density from 5.15 to 5.62 g cm-3 and a corresponding decrease in molar volume. This phenomenon is correlated to enhanced network connectivity and it was attributed to the alteration of Non-Bridging Oxygen (NBO) to Bridging Oxygen (BO) linkages. Consequently, an enhancement in mechanical properties is observed with increasing both Young’s (50.67 to 52.61 GPa) and Bulk (29.77 to 31.89 GPa) modulus, respectively. It is suggested that these factors result in enhanced glass rigidity and durability. The optical investigation demonstrates a broadening of the optical band gap from 3.01 to 3.30 eV. This suggests the presence of a denser glass network and declined glass electronic polarizability. The findings of the study indicated that the integration of low-level Yb2O3 into TZN-based glasses can result in a modification of the glasses properties, thereby highlighting the potential for advanced application in the domain of photonics.